HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA TENTANG PERAWATAN KHUSUS GIGI ANAK RETARDASI MENTAL DENGAN INDEKS KARIES ANAK - murika sari, nendika dyah ayu (JIKG (Jurnal Ilmu Kedokteran Gigi), 2019)
AbstractMental retardation is a condition of individuals with limited abilities which characterized by IQ index less than 70. Children with mental retardation tend to have poorer oral hygiene than their normal counterpart. The difficulties in oral hygiene due to lack of motoric skill, lack of parental attention and knowledge are the causes of the high caries index of children with mental retardation. This study aimed to determine the relationship between parental knowledge with the mental retardation children's caries index. A cross-sectional analytic study was conducted in this research. The study sample was 27 children aged 8-9 years. The data were collected using questionnaire of parental knowledge and an oral examination of caries index of children was recorded using DMF-T/def-t index. Data were tested by Chi Square test. The results showed an average DMF-T/def-t index 6.9 which was included in very high category. About 29.63% of the parents had the good knowledge (high category), 55.5% in medium category of parental knowledge, and 14.81% in low category. The result showed significant relationship between caries index in the child and parental knowledge (p=0.004, p<0.05). The conclusion of this study is that there was a significant relationship between the parental knowledge and mental retardation children's caries index.Keywords: mental retardation, caries index, parental knowledge